Pengembangan materi ajar fisika berbasis multirepresentasi untuk meningkatkan kemampuan berpikir analisis peserta didik di MAN 2 Makassar - Harti, Nining Dwi (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the validity of the product of multi-representation-based teaching materials, to determine the teacher's response to multi-representation-based teaching materials, to determine the students' responses to multi-representation-based teaching materials and to determine the effectiveness of multi-representation-based physics teaching materials. improve students' analytical thinking skills at MAN 2 Makassar. The experimental subjects of this study were 25 students of class X MIPA II MAN 2 Makassar. This research uses the ADDIE model development. The instruments used in this study were a multi-representation-based physics teaching material validation sheet, a teacher and student response questionnaire sheet, and a physics learning outcome test instrument. The results showed that the multi-representation-based physics teaching material in physics learning in class X MIPA II MAN 2 Makassar was valid with a validity content value of 0.74, the assessment of the educator's response to multi-representation-based physics teaching materials was in the very good/very practical category, response assessment students to multi-representationbased physics teaching materials are in the very good/practical category, the effectiveness of using multi-representation-based physics teaching materials is in the very good category. The effectiveness of multi-representation-based Physics teaching materials in learning is shown from the results of the Physics learning test with a percentage of 68% being above the KKM value